Characterization of mechanical properties of kenaf fibre reinforced polymer composite using orientation with angle variation - Zainal S.N.; Isa M.R.; Zaroog O.S.; Jalal M.F.A.; Sulaiman S.N.; Ismail I.N. (American Institute of Physics Inc., 2023)
In the past decades, the extensive studies had been accomplished on the natural fibre reinforced polymer composites (NFPC) and are still continuous until today. The composites made of natural fibre and polymer has proven the better effectiveness in high impact fatigue strength and toughness. The increases of fibre loading give higher results fundamental in strength due to its high interfacial bonding between the fibre. In the present work, experimental tests were carried out to study the mechanical properties; tensile, hardness and impact and morphological characterization: Scanning Electron Microscope (SEM) of the NFPC. The composites fabricated are between the Kenaf fibre and epoxy resin. The Kenaf fibre reinforced epoxy resin composites were fabricated using hand layup technique by layering the arranged fibre with polymer in the mould with different angle orientation (22.5 and 67.5) as the main parameter observed and the fibre composition (2%, 4% and 6%). Before the fabrication started, the fibre had undergone the alkali treatment for the effective surface modification that can enhance the interfacial bonding between the fibre. 2021 American Institute of Physics Inc.. All rights reserved.